1969
DOI: 10.1063/1.1652709
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reverse Current Due to the Brillouin Emf in a Diode

Abstract: It has been shown by Brillouin that, to satsify the second law of thermodynamics, a diode at finite temperature must generate a dc signal which just compensates the current resulting from the rectification of thermal noise. It is shown that this signal should actually be observable (as a spontaneous reverse current) when the diode is connected to a resistor at a lower temperature than itself. A successful experiment to observe the signal is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that both Brillouin's and Smoluchowki's ratchets can indeed generate power if operated out of equilibrium, where the laws of Thermodynamics do not apply . For instance, the diode and the resistor must be kept at different temperatures to enable direct current flow in Figure a, otherwise thermal fluctuations at the diode will compensate the current generated by the resistor . These concepts have inspired researches to create various devices functioning as ratchets.…”
mentioning
confidence: 99%
“…It has been demonstrated that both Brillouin's and Smoluchowki's ratchets can indeed generate power if operated out of equilibrium, where the laws of Thermodynamics do not apply . For instance, the diode and the resistor must be kept at different temperatures to enable direct current flow in Figure a, otherwise thermal fluctuations at the diode will compensate the current generated by the resistor . These concepts have inspired researches to create various devices functioning as ratchets.…”
mentioning
confidence: 99%
“…One needs at least two temperatures in heat engines. The impossibility of the rectification of thermal fluctuations by a simple diode-based circuit in isothermal conditions was explained by Brillouin in 1950, i.e., before Feynmann discussed his famous ratchet-and-pawl engine [20][21][22]. Nevertheless, it is possible to use a fluctuation rectifier with two diodes if they are switched in opposite directions, kept at different temperatures, and are connected by a capacitor.…”
Section: Discussionmentioning
confidence: 99%
“…Then, if the two compartments communicate by an additional channel, the device is expected to rectify thermal fluctuations and produce a net current of particles, which can deliver useful energy. For the last two concrete devices, it has been experimentally shown that they can work provided that the rectifier (ratchet-pawl or diode) is cooled at a lower temperature than the rest of the system [67,68] in return for the entropy decrease. Demons work in the same way once physically implemented.…”
Section: Maxwell's Demonmentioning
confidence: 99%